Exploring the Reactivity of Multicomponent Photocatalysts: Insight into the Complex Valence Band of BiOBr - Fang, Yan-Fen; Ma, Wan-Hong; Huang, Ying-Ping; Cheng, Gen-Wei (Chemistry : a European journal, 2013)
The band structure of multicomponent semiconductor photocatalysts, as well as their reactivity distinction under different wavelengths of light, is still unclear. BiOBr, which is a typical multicomponent semiconductor, may have two possible valence‐band structures, that is, two discrete valence bands constructed respectively from O 2p and Br 4p orbitals, or one valence band derived from the hybridization of these orbitals. In this work, aqueous photocatalytic hydroxylation is applied as the probe reaction to investigate the nature and reactions of photogenerated holes in BiOBr. Three organic compounds (microcystin‐LR, aniline, and benzoic acid) with different oxidation potentials were selected as substrates. Isotope labeling (H218O as the solvent) was used to determine the source of the O atom in the hydroxyl group of the products, which distinguishes the contribution of different hydroxylation pathways. Furthermore, a spin‐trapping ESR method was used to quantify the reactive oxygen species (.OH and .OOH) formed in the reaction system. The different isotope abundances of the hydroxyl O atom of the products formed, as well as the reverse trend of the .OH/.OOH ratio with the oxidative resistance of the substrate under UV and visible irradiation, reveal that BiOBr has two separate valence bands, which have different oxidation ability and respond to UV and visible light, respectively. This study shows that the band structure of semiconductor photocatalysts can be reliably analyzed with an isotope labeling method. Which isotope won? Hydroxylation in the BiOBr photocatalytic system with H218O solvent and 16O2 oxidant gives products with different isotope profiles under visible‐light versus UV irradiation (see scheme). The isotope abundance is also affected by the oxidative resistance of the substrate. Together with the .OH/.OOH ratio, the results show that BiOBr has two valence bands that have different oxidation abilities and responses to UV and visible light.